Cleopatra in space. Book two, The thief and the sword - Maihack, Mike (New York, NY : Graphix, an imprint of Scholastic, 2015)
A thief interrupts the school dance to steal the Sword of Kebechet, but Cleopatra is forbidden from pursuing him and remains at school, adjusting to her newfound popularity and responsibility because of a proprophecy that names her the savior of the galaxy.
Keywords: Graphic novels; Prophecies -- Fiction; Antiquities -- Fiction; Schools -- Fiction; Science fiction; Graphic novels